Body image perception, eating attitude and influence of media among undergraduate students of medical college in Delhi: a cross sectional study - Sharma, Manila; Singh, Sunil Kumar; Tiwari, Poornima; Chauhan, Nitesh (International Journal of Research in Medical Sciences, 2019)
Background: Body image perception is being shaped by unrealistic ideals portrayed in the media. Body dissatisfaction is one of the most consistent and robust risk factors for eating disorders, low self-esteem, depression, and obesity. Therefore, the objective of the current study is to ascertain the body image perception, abnormal eating attitudes and the role of media among undergraduate students of a medical college in Delhi, India. Methods: Cross-sectional study on 370 undergraduate medical students of Vardhman Mahavir Medical College and Safdarjung Hospital, New Delhi, India selected using stratified random sampling. India. Students completed a self-administered questionnaire which consist of demographic information, perceived body image, Eating Attitudes test (EAT-26) to assess eating attitudes, Socio Cultural Attitude Towards Appearance Questionnaire 3(SATAQ-3) scale for the role of media on body image perception. Data was analyzed using SPSS v21. Results: A total of 370 students (57.6% males and 42.4% females) aged 17-30 years, mean age of 20.30 years±2.02(SD). Abnormal body image perception was seen in 35.4%, 21.1% had abnormal eating attitude (EAT-26≥20), 36.5%, 40.5% agreed to be influenced by models and athletic figures in media respectively, 42.2% accepted that media was their source of information regarding standards of attractiveness, 27.6% felt pressured to be attractive according to SATAQ-3. Males more than females had disordered eating attitudes and felt media pressure to achieve an ideal body image. Significant association was observed between age and perceived body image (p=0.033), gender and EAT-26 score (p=0.039), EAT 26 and perceived body image (p=0.006), general internalization of media and perceived body image (p=0.003), internalization-general, internalization-athlete, media as source of information and EAT-26 score (<0.001, 0.001, 0.003 respectively). Conclusions: The media should take more responsibility to not represent unrealistic ideals of body image concerning both males and females. Educational and preventive efforts at institutional levels should be made to promote a healthy body image and eating behaviours.